Cut Elimination for Extended Sequent Calculi - Martini, Simone; Masini, Andrea; Zorzi, Margherita (Bulletin of the Section of Logic, 2023)
We present a syntactical cut-elimination proof for an extended sequent calculus covering the classical modal logics in the \(K\), \(D\), \(T\), \(K4\), \(D4\) and \(S4\) spectrum. We design the systems uniformly since they all share the same set of rules. Different logics are obtained by “tuning” a single parameter, namely a constraint on the applicability of the cut rule and on the (left and right, respectively) rules for \(\) and \(\). Starting points for this research are 2-sequents and indexed-based calculi (sequents and tableaux). By extending and modifying existing proposals, we show how to achieve a syntactical proof of the cut-elimination theorem that is as close as possible to the one for first-order classical logic. In doing this, we implicitly show how small is the proof-theoretical distance between classical logic and the systems under consideration.